Empirical Color Correction to MIST and PARSEC Isochrones on Gaia BR − RP and G − RP with Benchmark Open Clusters - Fan Wang; Min Fang; Xiaoting Fu; Yang Chen; Lu Li; Xiaoying Pang; Zhongmu Li; Jing Tang; Wenyuan Cui; Haijun Tian; Chao Liu (The Astrophysical Journal)
Recent literature reports a color deviation between observed Gaia color–magnitude diagrams (CMDs) and theoretical model isochrone predictions, particularly in the very low-mass regime. To assess its impact on cluster age determination via isochrone fitting, we quantified the color deviations for three benchmark clusters, Hyades, Pleiades, and Praesepe, both for the Gaia color (BP − RP) and ( G − RP). In general, the ( G − RP) color deviations are smaller than the (BP − RP) ones. Empirical color-correction functions based on these benchmarks are derived for the currently available MESA Isochrones and Stellar Tracks and PAdova and TRieste Stellar Evolution Code (PARSEC) 1.2S isochrone models. Applying the correction functions to 31 additional open clusters and 3 moving groups results in a significantly improved alignment between the isochrones and observed CMDs. With our empirical corrections, isochrones provide age estimates consistent with literature values obtained through the spectral lithium depletion boundary method, validating the effectiveness of our approach. The corresponding metallicities with PARSEC 1.2S also show a good agreement with the spectroscopic results. The empirical color-correction function we present in this work offers a tool for a consistent age determination within the full mass range of stellar clusters using the isochrone fitting method.